1995
DOI: 10.1007/bf00211787
|View full text |Cite
|
Sign up to set email alerts
|

Crankshaft motions of the polypeptide backbone in molecular dynamics simulations of human type-α transforming growth factor

Abstract: Order parameters for the backbone N-H and C alpha-H bond vectors have been calculated from a 150 ps molecular dynamics (MD) simulation of human type-alpha transforming growth factor in H2O solvent. Two kinds of 'crankshaft motions' of the polypeptide backbone are observed in this MD trajectory. The first involves small-amplitude rocking of the rigid peptide bond due to correlated changes in the backbone dihedral angles psi i-1 and phi i. These high-frequency 'librational crankshaft' motions are correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 26 publications
7
90
0
Order By: Relevance
“…Within the secondary structure elements of DHFR (Fig. S3), we observed that the crankshaft motion dominates the fluctuations of the peptide planes (27,51), in which the C α atoms essentially remain fixed and the largest displacements are observed for the carbonyl oxygens and amide protons. We also observed signs of coupling between the motions of peptide planes joined by hydrogen bonds within regular elements of secondary structure (35,50,52).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Within the secondary structure elements of DHFR (Fig. S3), we observed that the crankshaft motion dominates the fluctuations of the peptide planes (27,51), in which the C α atoms essentially remain fixed and the largest displacements are observed for the carbonyl oxygens and amide protons. We also observed signs of coupling between the motions of peptide planes joined by hydrogen bonds within regular elements of secondary structure (35,50,52).…”
Section: Discussionmentioning
confidence: 84%
“…qFit and related ensemble methods have an advantage over anisotropic B-factor description because they are not limited to unimodal distributions (48,49). The qFit model of the DHFR E:FOL:NADP+ complex contains information on the anisotropy and coupling of motions that has been observed from molecular dynamics and NMR measurements (25,35,(50)(51)(52). Within the secondary structure elements of DHFR (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In Fig. 1b, we provide a summary of the correlation analysis, where the crankshaft motion, a rotation of the peptide plane about the C a i À 1 -C a i axis that leads to the anti-correlation of c i À 1 and f i often observed in MD simulations, is shown in italics 24 . The crankshaft motion is equivalent to that put forward in the onedimensional Gaussian axial fluctuation model (1D-GAF) of the protein backbone and to the g motion of the related 3D-GAF motional model, the amplitudes of which have been extensively studied by NMR spectroscopy 20,21,[25][26][27] .…”
Section: Resultsmentioning
confidence: 99%
“…[7,[13][14][15] We have also calculated 2D CCR maps for the C'/C'ÀC a CCR rate, which demonstrate the strong dependence of this rate on the orientation of the C'-shift tensor and variations in s ab (Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…[7,9,[13][14][15] Whereas CCR processes in principle contain an enormous amount of information, the interpretation of these relaxation rates must be treated with great care. For example, a CSA/DD relaxation process depends on many factors, including the local molecular structure, the magnitude of the CSA and orientation of the shift tensor in the fixed molecular frame, and local anisotropic dynamics.…”
mentioning
confidence: 99%